Nature of Crack Path Instabilities in Thin Sheets Cut by Blunt Objects - Hamm-Hahn, L (American Physical Society, 2020)
Cutting a brittle thin sheet with a blunt object leaves an oscillating crack that seemingly violates the principle of local symmetry for fracture. We experimentally find that at a critical value of a well chosen control parameter the straight propagation is unstable and leads to an oscillatory pattern whose amplitude and wavelength grow by increasing the control parameter. We propose a simple model that unifies this instability with a related problem, namely that of a perforated sheet, where through a similar bifurcation a series of radial cracks spontaneously spiral around each other. We argue that both patterns originate from the same instability. © 2020 American Physical Society.